Բրազիլահայ համայնքի պատմութիւնից - Հովհաննիսեան, Արա (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Статья посвящена армянской общине Бразилии. В ней подробно рассказывается о переселении армян в Бразилию и предпринимается попытка выяснить количество армян, проживающих в этой стране. Описывается процесс формирования армянской общины и общинных организаций в Бразилии. В статье также говорится о значительной роли Армянской Церкви в жизни диаспоры. Обсуждаются все те проблемы, которые существуют в армянской общине. В конце статьи рассказывается об основных видах деятельности армян Бразилии и отмечается все достижения и успехи общины за время своего существования. The article is dedicated to the Armenian community of Brazil. It begins with a detailed account of the resettlement of the Armenians in Brazil. An attempt is made to find out the number of Armenians living in this country. The process of formation of the Armenian community and community organizations in Brazil are described. The article also talks about the significant role of the Armenian Church in the life of the Diaspora. All the problems existing in the Armenian community of Brazil are discussed. At the end of the article, it mentions the main activities of the Armenians in Brazil and notes all the achievements and success that the Armenian Diaspora has managed to achieve during its existence.
Keywords: Հայոց պատմություն; Հայ գաղթօջախներ